2021
DOI: 10.1109/jsen.2020.3032438
|View full text |Cite
|
Sign up to set email alerts
|

sCrop: A Novel Device for Sustainable Automatic Disease Prediction, Crop Selection, and Irrigation in Internet-of-Agro-Things for Smart Agriculture

Abstract: Agriculture Cyber-Physical System (A-CPS) is becoming increasingly important in enhancing crop quality and productivity by utilizing minimum cropland. This paper introduces the innovative idea of the Internet-of-Agro-Things (IoAT) with an explanation of the automatic detection of plant disease for the development of ACPS. Majority of the crops were infected by microbial diseases in conventional agriculture. Also, the constantly mutating pathogens cannot be known to the knowledge of the farmer, due to which, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…The IoT‐Irrigation is a dynamic irrigation scheduling system (AgriSens) to manage water for agricultural land. AgriSens provides real‐time, automated, and dynamic processing at various stages of a crop life cycle using populations 7 such as remote manual irrigation.…”
Section: Related Workmentioning
confidence: 99%
“…The IoT‐Irrigation is a dynamic irrigation scheduling system (AgriSens) to manage water for agricultural land. AgriSens provides real‐time, automated, and dynamic processing at various stages of a crop life cycle using populations 7 such as remote manual irrigation.…”
Section: Related Workmentioning
confidence: 99%
“…Pest detection and recognition have been performed through k-means clustering and correspondence filter [149]. CNN based models have been used in [150] and in [151] in crop disease detection.…”
Section: Pest/disease Controlmentioning
confidence: 99%
“…The experimental results showed that this method achieved good results in the corn leaf database. Udutalapally et al proposed a method to distinguish wheat pest leaves based on imaging hyperspectral technology from the perspective of optics, constructed a spectral ratio fingerprint feature based on the relative change of spectra, preferentially selected several imagebased geometric and texture features in a targeted manner, and achieved very promising recognition ability for wheat in the experiments [8].…”
Section: Related Workmentioning
confidence: 99%